The campus image: using social media to design for place attachment - Hupe, Blaine (Kansas State University, 2024)
This study aims to understand place attachment on college campuses through social media images. Place attachment is defined as the love for a place (Tuan, 1977). While place attachment has been studied for decades, less attention has been paid to the potential of new technology as a tool for place attachment studies. This study fills the gap by examining place attachment to campus landscape features in visual social media posts, guided by a question, what landscape features contribute most to students’ place attachment on campus, and can they be captured on social media? College campuses are settings with high levels of place attachment and high use of social media by students sharing their campus experiences. This study collected over 3,500 images of college campuses across the United States from Instagram, a popular visual social media platform among college students. Thematic analysis revealed patterns and correlations between place attachment and the physical landscape features pictured in posts. These findings offer insights into designing college campuses for place attachment and contribute to the existing body of literature by confirming social media analysis as a method for place attachment studies. Further, the findings from the research informed a framework of recommended design takeaways for re-designing the Kansas State University campus core area.
Keywords: Place attachment; Campus design; Social media analytics; Kansas State University